GABPA-Mediated Expression of HPN-AS1 Facilitates Cell Apoptosis and Inhibits Cell Proliferation in Hepatocellular Carcinoma by Promoting eIF4A3 Degradation - Hu, Ying; Sun, Xiaoli; Li, Bing Lin; Xu, Ruiling; Shao, Jing; Zhao, Lei; Liu, Jingyang; Zhang, Xu; Ning, Dandan; Jin, Shizhu (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Hepatocellular carcinoma (HCC) represents a common neoplasm that presents a substantial worldwide health challenge. Nevertheless, the involvement of HPN-AS1 in HCC remains unknown. Materials and Methods: The quantitative reverse transcription polymerase chain reaction (qRT-PCR) assay was utilized to measure HPN-AS1 expression in HCC. The GABPA effects on the HPN-AS1 promoter were analyzed through chromatin immunoprecipitation and luciferase reporter assays. Cell proliferation potential was determined by deploying CCK-8 assay, Ki-67 immunofluorescence staining, and colony formation assay. Cell apoptosis was detected using acridine orange/ethidium bromide staining and terminal deoxynucleotidyl transferase dUTP nick end labeling staining. Western blotting was utilized to measure the protein levels of proliferation factors and apoptosis regulators. HPN-AS1 binding to eIF4A3 was accessed by RNA-binding protein immunoprecipitation assay. Results: HPN-AS1 was significantly downregulated in both HCC cells and tissues. Lower HPN-AS1 levels indicate a poorer HCC prognosis. Moreover, we found that GABPA functions as a transcription factor for HPN-AS1. Functional studies revealed that HPN-AS1 displayed inhibitory effects on HCC cell proliferation and promoted apoptosis. Mechanically, HPN-AS1 bound to and facilitated translation initiation factor eIF4A3 degradation. Loss of HPN-AS1 augmented eIF4A3 protein levels rather than eIF4A3 mRNA levels. Exogenous expression of eIF4A3 could restore eIF4A3 protein levels and reverse HPN-AS1 overexpression-induced cell proliferation inhibition and cell apoptosis. Conclusion: Our study elucidated that HPN-AS1 downregulation was mediated by GABPA. HPN-AS acted as a tumor suppressor within HCC through binding and facilitating eIF4A3 degradation. The study provides a novel insight into the biological function of HPN-AS1 in HCC, suggesting that HPN-AS1 could be a promising biomarker and a potential target for HCC diagnosis and treatment. Cite this article as: Hu Y, Sun X, Li BL, et al. GABPA-mediated expression of HPN-AS1 facilitates cell apoptosis and inhibits cell proliferation in hepatocellular carcinoma by promoting eIF4A3 degradation. Turk J Gastroenterol. 2024;35(7):577-586.